Construção coletiva de um saber sobre a floresta na definição dos indicadores de sustentabilidade da Reserva Legal do assentamento Olga Benário - Machado, Antonio Maciel Botelho (2011)
This research aimed to build knowledge about the forest by studying sustainability indicators of the legaly protected reserve ( reserva legal ) of the agrarian reform rural settlement Olga Benário, in Santa Tesersa do Sul, Western Paraná State, Southern Brazil. It has Marx's historical materialism as guideline, though considering rural dweller's praxis in their productive action over the land and in their reflections together with the researcher. The starting point was the social representations about the living site and a new approach was built through debates, site visits, colective practices. This new approach afforded a perspective of totality which was able to include the legal reserve in the project of the rural settlement. After defining this totality as an agroecosystem and expliciting their possibilities and limits in what they projected for it, it was able to define the level of sustainability they wished to the reserva legal as part of the system. We confirmed the initial statement that a participative research process would lead to build new knowledge about the forest, among settled members of Brazilian Landless Workers' Movement (MST). This was confirmed by the final capacity of the group in defining the sustainability levels they wished, in drawing activities for the future, and in involving themselves immediately in practices of forest restoration in their reserve. The matrix of sustainability indicators of the reserve of the settlement that was built by the group was seen as processual, dynamic and transitory once any future intervention in the agroecosystem, including the forest subsystem, would result in new social representations as a caleidoscope. These new representations, by their turn, will orient new knowledge and practices which will themselves constitute, dialectly, new social contexts, what will demand new studies and practices by this social group.